Peningkatan Daya Saing Produk UMKM Melalui Pelatihan Branding Emosional dan Pengemasan Ramah Lingkungan Bagi Ibu PKK Desa Asinan, Kabupaten Semarang - Tri Imaliya; Herty Ramayanti Sinaga; Pindo Asti; Ivan Permana; Gibson Manalu; Daniel Adi Setya Rahardjo; Kusna Djati Purnama (Pusat Riset dan Inovasi Nasional, 2025)
Modern marketing requires a distinctive product identity to attract potential buyers. This community engagement activity aimed to enhance the competitiveness of Pokja 2 MSME products managed by PKK women in Asinan Village, Semarang Regency, through training on emotional branding and eco-friendly packaging. The main challenges faced by the community partners included a lack of understanding in crafting brand narratives that appeal to consumers’ emotions and the use of packaging that did not align with sustainable principles. The training was delivered through a participatory approach combining interactive lectures, group discussions, and hands-on practice, conducted offline on June 16, 2025, at the Asinan Village Hall. A total of 30 participants representing PKK groups from neighborhood to village level actively took part in the sessions. The results indicated a significant improvement in participants’ understanding of the importance of product storytelling that reflects values such as family ties, local identity, and consumer empathy. This was evidenced by the pre-test and post-test results, showing an increase in branding comprehension from 24% to 84%.